Extending understanding of latitudinal patterns in parasitoid wasp diversity. Issue 1 (2nd October 2015) - Timms, Laura L.; Schwarzfeld, Marla; Sääksjärvi, Ilari E.
Abstract: While the diversity of most taxa increases from temperate to tropical regions, the parasitoid wasp family Ichneumonidae has often been cited as an example of an anomalous diversity pattern with their highest diversity at mid‐latitudes. A rich body of literature has attempted to explain this pattern and provide hypothesised mechanisms, and recent studies have suggested that the pattern may result from biases in the data. Previous studies of patterns in ichneumonid diversity have mined catalogue data or have compared collections from tropical and temperate areas across a limited range of latitudes. Few studies are available that include species richness for all subfamilies, and none have been from regions above 60°N. To increase the number of datasets available to address these patterns, we first tested the assumption that subfamily abundance can be a strong predictor of species richness. We then compared abundances of ichneumonid subfamilies in field collections from a wide range of latitudes (25°S–81°N), and used generalised additive models to evaluate characteristics of the subfamilies as predictors of the observed patterns. We demonstrate a wide variety of latitudinal patterns, reflecting the ecological variation between subfamilies. In addition, our models show that host taxon and subfamily identities are better predictors of the shape of the relationship between subfamily abundance and latitude than other characteristics that have been previously hypothesised to be important, including parasitoid life history strategy and body size.